2010
DOI: 10.1089/jmf.2009.0050
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavone Composition, Total Polyphenolic Content, and Antioxidant Activity in Soybeans of Different Origin

Abstract: Twenty soybean cultivars, originating from the United States, Russia, Serbia, and China, were analyzed for their isoflavone composition, total polyphenolic content, and antioxidant activity. Isoflavones were extracted by aqueous methanol (80%) and analyzed by high-performance liquid chromatography=diode array detection. Precision and linearity of the applied method were within the standard limits of validation. The highest and the lowest total isoflavone contents were 4.59 and 1.45 mg=g of dried soybean weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 27 publications
6
20
2
Order By: Relevance
“…Average isoflavone content among all analyzed cultivars was 2.97 mg/g, which corresponds to previous results obtained from 20 cultivars of yellow seed for which average total isoflavone content was 3.25 mg/g. 31 The average value of isoflavones obtained is considerably higher than those reported in a study performed in the United States (1.86 mg/g) 32 or in India (1.05 mg/g). 6 Black and green seed varieties showed higher content of total isoflavones (3.16-3.58 mg/g) compared with other colored seeds, although the yellow variety had the highest total isoflavone content.…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…Average isoflavone content among all analyzed cultivars was 2.97 mg/g, which corresponds to previous results obtained from 20 cultivars of yellow seed for which average total isoflavone content was 3.25 mg/g. 31 The average value of isoflavones obtained is considerably higher than those reported in a study performed in the United States (1.86 mg/g) 32 or in India (1.05 mg/g). 6 Black and green seed varieties showed higher content of total isoflavones (3.16-3.58 mg/g) compared with other colored seeds, although the yellow variety had the highest total isoflavone content.…”
Section: Resultscontrasting
confidence: 53%
“…31,35 This points out the primary role of isoflavones in plants, being predominantly hormonal substances and exhibiting less potent antioxidant activity compared with some other components.…”
Section: Resultsmentioning
confidence: 99%
“…The anti-oxidant activity can be caused by the phenolic compounds in soybean products [5,6]. Soybean isoflavones have multiple beneficial health effects, especially on estrogen-deficiency conditions such as menopausal symptoms [7] and exhibit high anti-tyrosinase activity [8].…”
Section: Introductionmentioning
confidence: 99%
“…Wang and Murphy (1994) reported that in analyzed conditions the sites have less influence than the harvesting year. In our previous work, we showed that soybean genotype plays a significant role in the content and the composition of isoflavones in soybeans, while the origin of soybeans does not have a major impact on these characteristics (Tepavčević et al, 2010). Inheritance of isoflavone content in soybeans is poorly documented, although some genetic effects that underlie the isoflavone content in soybean seeds have been identified (Liang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%